Morphological classification and origin of lake depressions in Mongolia - Enkhbold, Altanbold; Khukhuudei, Ulambadrakh; Doljin, Dash (Proceedings of the Mongolian Academy of Sciences, 2021)
An improved classification of the origin of lake depressions due to geological, geomorphological factors and climate change is a requirement of the day in Mongolia. We present a new holistic classification using comparative analysis method. This study suggests a two-tier classification in terms of origin and morphological feature of the lakes, which replaces the previous one-tier classification. Mongolia has identified 11 main and 26 subtypes of origin, and 8 main types of morphology, based on the features of 32 lake depressions. The result of the study shows that the lakes of Mongolia developed in 3 stages, first, affected by tectonic movement, followed by glacial and finally, owing to other exogenic factors. This morphological classification study will create the basic conditions for preserving and using these lakes more efficiently and ecologically in the future by making the classification of the origin of lake depression.